El rol de la enfermera en la educación sexual integral en adolescentes de 12 a 15 años de la Unidad Educativa Humberto Moreira Márquez, Cantón Ventanas, octubre 2018 – abril 2019 - Macías Escobar, Kerly Narcisa (2019)
This research focuses on the study of the role of nursing as an essential element in the comprehensive sexual education of adolescents, considering that there is confusion in topics such as sex, sexuality, adolescent pregnancies, bodily acceptance and bio-psycho-social development that are proper of this stage. The objective of the research is to determine the role of the nurse in comprehensive sexual education in adolescents between 12 and 15 years of age in the Humberto Moreira Márquez Educational Unit, Ventanas canton, October 2018 - April 2019. The research was designed methodologically from the analytical and synthetic methods, which allowed to know in a descriptive way what was happening inside the educational institution. Inductive and deductive methods were used that started from specific cases to general cases related to Comprehensive Sexual Education and through the field study applied to the 83 adolescents between 12 and 15 years of age, we were able to obtain data that allowed us to design the solution proposal. From the data obtained in the field study it was possible to obtain that 56% of the students have confusion about essential ESI topics, in addition 89.11% of them stated that the teachers do not show an interest in this type of subject and that the educational role of the nursing staff is deficient in this type of interventions. Therefore, it is concluded that ignorance of the issues related to comprehensive sexual education in adolescents is due to the poor information provided by nursing staff and teachers.